The effect of Statistics Anxiety toward Statistics Course’s Achievement in Psychology Students - Aries Yulianto (Institute of Computer Science (IOCS), 2022)
Statistics courses are crucial since they represent formal exposure to research methods and to afford students analytical skills. On the contrary, many university students taking statis-tics courses report statistics anxiety, particulary psychology students. Howover, there were few studies about relationship between statistics anxiety and achievement in statistics course among undergraduate psychology students. Objective of this study is to investigate effect of statistics anxiety on statistics course achievement among students of psychology. Respondents were 69 psychology students (53 women, 16 men) from a private university at Jakarta, who enrolled statis-tics course. Statistics anxiety were measured by adaptation of STARS (Statistical Anxiety Rating Scale), consists of 20 items with 4-point Likert-type scale, which measures five theoretical components, i.e. test and class anxiety, computation self-concept, worth of statistics, fear of asking for help, and fear of statistics teachers. Cronbach’s alpha coefficient for reliability was .819 for the entire scale. Results showed that achievement in statistics course were not significantly affected by statistics anxiety, R2 = .007, F(1, 67)= .493, p = .485. Surprisingly, age have negatively significant effect to statistics course’s achievement. Moreover, women have higher statistics anixety than men.